Analysis of Post-Listing Price Movements of Selected Company Shares - Eswaran, R. (Indian Journal of Finance, 2009)
Every company needs finance for its inception and functioning. It needs finance to raise its fixed and variable assets. Hence, the requirement may be for short term or for long term. The short term needs can be met through loans and other facilities available in the banks and financial institutions or even by accepting fixed deposits from the public. For the long term requirement, also, it can approach the banks and financial institutions but the burden of paying the interest is heavy. It can raise money through public issue of equity, it need not pay interest rate. But, it has to comply with the rules and regulations of the SEBI and the RBI. The present study has been undertaken with the objectives of analyzing the growth of primary market, the performance of different industries, selected scrips in the primary market and the volatility in the post listing return of the selected scrips.